Antifungal activity and inhibition of fumonisin production by Rosmarinus officinalis L. essential oil in Fusarium verticillioides (Sacc.) Nirenberg. (1st January 2015) - da Silva Bomfim, Natalia; Nakassugi, Lydiana Polis; Faggion Pinheiro Oliveira, Jessica; Kohiyama, Cassia Yumie; Mossini, Simone Aparecida Galerani; Grespan, Renata; Nerilo, Samuel Botião; Mallmann, Carlos Augusto; Alves Abreu Filho, Benicio; Machinski, Miguel
Highlights: The essential oil of Rosmarinus officinalis exhibited chemopreventive effects. The essential oil exhibited strong antifungal activity against F. verticillioides . Rosemary essential oil caused leakage of the cytoplasm of the fungus. The results indicated that this essential oil inhibited the production of fumonisins. The essential oil could be used as a potential source of eco-friendly fungicides. Abstract: The chemical composition of Rosmarinus officinalis L. essential oil (REO) was analysed by gas chromatography–mass spectrometry and nuclear magnetic resonance spectroscopy. The main compounds of the REO were 1.8 cineole (52.2%), camphor (15.2%) and α-pinene (12.4%). The mycelial growth of Fusarium verticillioides (Sacc.) Nirenberg was reduced significantly by 150 μg/mL of REO. Significant microscopic morphological changes were visualised, such as the rupture of the cell wall and the leakage of cytoplasm at 300 μg/mL of REO. At lower concentrations of REO, the effects on the production of ergosterol and the biomass of mycelium varied, as did the effects on the production of fumonisins, but at ⩾300 μg/mL of REO, these processes were significantly inhibited, showing the effectiveness of the REO as an antifungal agent. The results suggested that the REO acts against F. verticillioides by disrupting the cell wall and causing the loss of cellular components, subsequently inhibiting the production of fumonisins and ergosterol.